International trade and unemployment: The worker-selection effect - Marco de Pinto; Jochen Michaelis (Philipps-University Marburg, Faculty of Business Administration and Economics, 2011)
This paper analyzes how trade liberalization influences the unemployment rate of workers with different abilities. We refine the Melitz (2003) framework to account for trade unions and heterogeneous workers, who differ with respect to their abilities. Our main findings are: (i) highability workers profit from trade liberalization in terms of higher wages and higher employment; (ii) the least efficient workers loose their job and switch to long-term unemployment (worker-selection effect); (iii) if a country is endowed with a large fraction of low-skilled workers, trade liberalization leads to a rise in aggregate unemployment. In this case, trade liberalization may harm a country's welfare.
Keywords: F1; F16; J5; 330; trade liberalization; trade unions; skill-specific unemployment; Außenhandelsliberalisierung; Arbeitslosigkeit; Qualifikation; Personalauswahl; Beschäftigungseffekt; Theorie